Feedback-Seeking Behavior and Leader-Member Exchange: Do Supervisor-Attributed Motives Matter? - Lam, Wing; Huang, Xu; Snape, Ed (Academy of Management Journal, 2007)
We investigated how supervisors' interpretations of what motivates their subordinates' feedback-seeking behavior were related to both the quality of leader-member exchange and subordinates' work performance. Using a sample of 499 supervisor-subordinate dyads collected in China in two studies, we found that subordinates' feedback seeking was positively related to the quality of leader-member exchange and objective work performance only when supervisors interpreted the feedback-seeking behavior as being driven more by performance enhancement motives and less by impression management motives.